Validation of the TOPAS Monte Carlo toolkit for HDR brachytherapy simulations - Berumen, Francisco; Ma, Yunzhi; Ramos-Méndez, José; Perl, Joseph; Beaulieu, Luc (Brachytherapy, 2021)
The goal of this work is to validate the user-friendly Geant4-based Monte Carlo toolkit TOol for PArticle Simulation (TOPAS) for brachytherapy applications. Brachytherapy simulations performed with TOPAS were systematically compared with published TG-186 reference data. The photon emission energy spectrum, the air-kerma strength, and the dose-rate constant of the model-based dose calculation algorithm (MBDCA)-WG generic Ir-192 source were extracted. For dose calculations, a track-length estimator was implemented. The four Joint AAPM/ESTRO/ABG MBDCA-WG test cases were evaluated through histograms of the local and global dose difference volumes. A prostate, a palliative lung, and a breast case were simulated. For each case, the dose ratio map, the histogram of the global dose difference volume, and cumulative dose-volume histograms were calculated. The air-kerma strength was (9.772 ± 0.001) × 10−8 U Bq−1 (within 0.3% of the reference value). The dose-rate constant was 1.1107 ± 0.0005 cGy h−1 U−1 (within 0.01% of the reference value). For all cases, at least 96.9% of voxels had a local dose difference within [−1%, 1%] and at least 99.9% of voxels had a global dose difference within [−0.1%, 0.1%]. The implemented track-length estimator scorer was more efficient than the default analog dose scorer by a factor of 237. For all clinical cases, at least 97.5% of voxels had a global dose difference within [−1%, 1%]. Dose-volume histograms were consistent with the reference data. TOPAS was validated for high-dose-rate brachytherapy simulations following the TG-186 recommended approach for MBDCAs. Built on top of Geant4, TOPAS provides broad access to a state-of-the-art Monte Carlo code for brachytherapy simulations.